Design of Decentralized Adaptive Sliding Mode Controller for the Islanded AC Microgrid With Ring Topology - Jiang, He; Wei, Mofan; Zhao, Yan; Han, Ji (Frontiers in Energy Research, 2021)
Sliding mode control can restrain the perturbations generated from the intermittence of the renewable energy generation and the randomness of local loads when microgrids are operating in islanded mode. However, the microgrid consists of several subsystems and the interactions among them will cause the chattering problems under the overall sliding mode control. In this paper, the chattering restraint issues for voltage control of the islanded microgrid with a ring topology structure are investigated based on the decentralized adaptive sliding mode control strategies. Firstly, we construct a tracking error system with interconnections considering the power transmission among subsystems and nominal values of system states. Secondly, we design linear matrix inequalities (LMIs) according to the H∞ attenuation performance of the system external disturbances. Then, the tracking error performance and the control precision are guaranteed via the asymptotic stabilities of integral sliding mode surfaces. Adaptive laws are utilized to address the chattering problems of the sliding mode control. Finally, simulation results verify the effectiveness of the proposed decentralized control methods.